If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = -5(6n + -6) Reorder the terms: 60 = -5(-6 + 6n) 60 = (-6 * -5 + 6n * -5) 60 = (30 + -30n) Solving 60 = 30 + -30n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '30n' to each side of the equation. 60 + 30n = 30 + -30n + 30n Combine like terms: -30n + 30n = 0 60 + 30n = 30 + 0 60 + 30n = 30 Add '-60' to each side of the equation. 60 + -60 + 30n = 30 + -60 Combine like terms: 60 + -60 = 0 0 + 30n = 30 + -60 30n = 30 + -60 Combine like terms: 30 + -60 = -30 30n = -30 Divide each side by '30'. n = -1 Simplifying n = -1
| 38-n=5+4(-2n+3) | | -26+6p=-8(1-3p) | | 2(r+4)=-35 | | 580=-20b | | 9y+12=84 | | 21x-3=40x | | 2(3-x)=60 | | -5.5=-3.4 | | 7(x-2)=5(x-4) | | -7(7n+7)=39-5n | | 3+r=19 | | 10b^2-15b-8b+12b=0 | | 12x^4+10x^3-12x^2=0 | | -3n-2(-8n-3)=-14+3n | | 6x+12+54=180 | | 18x+6=19x | | 2(2p-3)=36-2p | | 8(8x-1)+4(1+8x)=-4 | | -23=6x+2 | | 16x^2-72x+75=0 | | 9x+6=-36 | | 32=-6x+2 | | 69-1=9+20 | | 17x+20=16x+20 | | 10x+1=9x+12 | | -23=6*4+2 | | x+77+x+62=45 | | 32=-6*-5+2 | | 58=-6*-7+2 | | 2x-5=4.4 | | 68=-6*-10+2 | | 4x-10-3x-(x-7)= |